2005
DOI: 10.1111/j.0011-1348.2005.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, Threat and the Labeling of Convicted Felons*

Abstract: Florida law allows judges to withhold adjudication of guilt for persons who have either pled guilty or been found guilty of a felony. This provision may apply only to persons who will be sentenced to probation, and it allows such individuals to retain all civil rights and to truthfully assert they had not been convicted of a felony. This paper examines the effects of race and Hispanic ethnicity on the withholding of adjudication for 91,477 males sentenced to probation in Florida between 1999 and 2002. Hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 48 publications
7
133
2
Order By: Relevance
“…They found that racial typification of crime was a significant predictor of policy punitiveness. Shortly thereafter, Bontrager, Bales, and Chiricos (2005) used the racial threat perspective to guide their examination of the effect of race and ethnicity on the withholding of adjudication. The results of their analyses showed that Hispanics and blacks are significantly less likely than whites to have adjudication withheld when other individual and community level factors are controlled for.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that racial typification of crime was a significant predictor of policy punitiveness. Shortly thereafter, Bontrager, Bales, and Chiricos (2005) used the racial threat perspective to guide their examination of the effect of race and ethnicity on the withholding of adjudication. The results of their analyses showed that Hispanics and blacks are significantly less likely than whites to have adjudication withheld when other individual and community level factors are controlled for.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such propositions have been widely tested in relation to pretrial release (Free 2004, Nagel 1983, sentencing (Bontrager, Bales and Chiricos 2005;Feldmeyer and Ulmer 2011;Jacobs and Carmichael 2002;Ruddell and Urbina 2004;Stolzenberg, D'Alessio and Eitle 2004;Wang 2012;Wang and Mears 2010), the size of police forces (Chamblin 1989;Stults and Baumer 2007), arrest (Chamlin and Liska 1992;Liska and Chamlin 1984;Parker, Stults and Rice 2005) and police use of deadly force (Liska and Yu 1992). Two studies on Louisiana voting patterns reveal a potential impact of changes in African-American populations on white voting patterns (Giles and Buckner 1998;Giles and Hertz 1994).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the explanatory power of models, some researchers incorporate measures of courtroom context, including judge level variables, and external environments, such as political forces (Bontrager et al 2005;Johnson 2005;Myers and Talarico 1987;Ulmer 2012;Ulmer and Johnson 2004;Ward et al 2009). Several researchers seek to isolate the effects of the demographic and racial composition of various actors in the criminal justice system, including judges (Spohn 1990;Tiede et al 2010;Welch et al 1988;Wooldredge 2010), prosecutors (Ward et al 2009), and the local legal profession (King et al 2010).…”
Section: The Judge Within Social Science Research: Sentencing Patternsmentioning
confidence: 99%
“…Such propositions have been widely tested in relation to pretrial release (Free Jr. 2004;Nagel 1983), sentencing (Bontrager et al 2005;Feldmeyer and Ulmer 2011;Jacobs and Carmichael 2002;Ruddell and Urbina 2004;Stolzenberg et al 2004;Wang 2012;Wang and Mears 2010), the size of police forces (Chamlin 1989;Stults and Baumer 2007), arrest (Chamlin and Liska 1992;Liska and Chamlin 1984;Parker et al 2005) and police use of deadly force (Liska and Yu 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that racial typification of crime was a significant predictor of policy punitiveness. Shortly thereafter, Bontrager et al (2005) used the racial threat perspective to guide their examination of the effect of race and ethnicity on the withholding of adjudication. The results of their analyses showed that Hispanics and Blacks are significantly less likely than whites to have adjudication withheld when other individual and community level factors are controlled for.…”
Section: Literature Reviewmentioning
confidence: 99%